The regulation of insulin secretion via phosphoinositide-specific phospholipase Cβ signaling. (January 2019) - Hwang, Hyeon-Jeong; Jang, Hyun-Jun; Cocco, Lucio; Suh, Pann-Ghill
Abstract: Phospholipase Cβ (PLCβ) is a membrane-associated enzyme activated by membrane receptors, especially G-protein coupled receptors (GPCRs). It propagates intracellular signaling by mediating phospholipid metabolism and generating key second messengers, such as inositol triphosphate and diacylglycerol, leading to intracellular Ca 2+ mobilization and activation of kinases, such as protein kinases C. In pancreatic β-cells, PLCβ-mediated signaling activated by various factors, such as free fatty acids and neuronal and hormonal ligands, has been confirmed as being involved in the regulation of insulin secretion, and PLCβs have been regarded as essential mediators for augmenting insulin secretion. In this review, we describe the physiological function of PLCβs in the regulation of glucose-stimulated insulin secretion and discuss emerging data on GPCR/PLCβ signaling that is being developed as a target for the treatment of diabetes mellitus.